miR-30b-5p acts as a tumor suppressor microRNA in esophageal squamous cell carcinoma - Xu, Jianfeng; Lv, Haiyan; Zhang, Bo; Xu, Feng; Zhu, Hongyu; Chen, Baofu; Zhu, Chengchu; Shen, Jianfei (Journal of Thoracic Disease, 2019)
Background: To study miR-30b-5p expression in esophageal squamous cell carcinoma (ESCC) by comparisons between tumor tissues and matched adjacent non-cancerous tissues to elucidate the correlation between miR-30b-5p expression and ESCC clinical parameters, and to explore the signaling pathways associated with miR-30b-5p and key target genes. Methods: Clinical data, cancer tissues, and adjacent non-cancerous tissues of 32 patients diagnosed with ESCC were collected from Taizhou Hospital of Zhejiang Province. The expression levels of miR-30b-5p were determined by real-time polymerase chain reaction (RT-PCR). mRNA data for ESCC tissues and normal tissues, and clinical materials of patients with ESCC were obtained from the Gene Expression Omnibus (GEO) database and The Cancer Genome Atlas (TCGA). Associations between miR-30b-5p expression and clinical features of patients with ESCC and overall survival were explored. A bioinformatics analysis was performed to determine the pathways and key miR-30b-5p targets associated with ESCC. Additionally, a cytological experiment was performed to evaluate the biological functions of miR-30b-5p. Finally, correlations between miR-30b-5p and key targets involved in PI3K/Akt signaling pathways were validated by western blotting. Results: The expression level of miR-30b-5p in the 32 ESCC tissues was significantly lower than that in adjacent normal tissues (P